Servicios financieros y mitigación de choques al consumo en los hogares rurales colombianos (2021)
This research assesses whether access to a savings account and, in general, to the financial system can mitigate the impact of exogenous shocks to rural household consumption in Colombia. Using data from the Colombian Longitudinal Survey of the University of the Andes (ELCA) for the year 2013, it is found that the impact of exogenous shocks on the rural population can be divided into three categories of shocks recently suffered by rural households. To quantify the impact, the sample of households are divided into those that currently have a savings account and those that do not, and the effect of the shock on the household's monthly food consumption is then estimated. The results of the regressions carried out are not conclusive because the coefficients are not significant enough. However, the estimated coefficients suggest that having a savings account can have a smoothing effect on household consumption. This finding may encourage...